The Sacred Writing of Knowledge: Interpreting the True Form Charts of the Man-Bird Mountain in Taoism - Cai, Linbo (Religions, 2022)
The True Form Charts of the Man-Bird Mountain (人鳥山真形圖, or TFCMBM) are important ritual images created by ancient Taoists. Scholars envisage them as the “fairy mountain map” (仙山圖) or “fairyland picture” (仙境圖) imagined by ancient Taoists. However, TFCMBM is actually a description of the mechanism of the “convergence of celestial and terrestrial qi”(天地氣交) in the human body. According to ancient Chinese medicine, the mechanism of the inter-induction of qi (氣交) controls the transmission and transformation of food, circulation of qi-blood in the body, and generation and storage of vital essence. Ancient Taoist priests referred to the mechanism of the inter-induction of qi as “regulating qi in Central Yellow” (黃中理炁) and as a kind of image, “the true shape of the human bird mountain” to guide novice Taoists in meditation (存思) and activating qi (行氣). This study argues that the TFCMBM is a portrayal of the mechanism of the inter-induction of qi and reveals the Taoist method of writing sacred knowledge and its cognitive nature.